Advances in deep learning applications for smart cities - Kumar, Rajeev; Dwivedi, Rakesh Kumar 1973- (Advances in electronic government, digital divide, and regional development (AEGDDRD) book series, 2022)
Emergence of smart city : smart city / Anu Sharma, RK Dwivedi -- An application for human resource and humanoids management for smart city / Abhay Saxena, Ashutosh Bhatt -- Human-machine interactions' a synthesis of threats and opportunities / Priyadarsini Patnaik -- Machine learning applications to smart city : a comparative study / Nikita Malik, Menal Dahiya, Nipun Walia -- Object detection methods for improving smart city safety / Kavita Srivastava -- Emergence of smart city concept : smart city / Anu Sharma, RK Dwivedi -- Challenges and opportunities for SMART meters in smart cities of India using machine learning and deep learning / Rupal Gupta, Ruchika Gupta -- Machine learning in automobiles / Preety Khatri, Rohit Kumar. "This book provides both a foundational base of knowledge around deep learning and blockchain application for smart cities and explore plentiful ways that smart cities of the future must aspire to accommodate increasing technology and their expectations of, modern living, integrated societies, knowledge-based workforce, factory automation, virtual-real social behaviors and more.